Problem-Based Learning in an Online Reading Course to Stimulate Critical Thinking Skills - Dewi Suriyani Djamdjuri; Maeleni Maeleni (STKIP PGRI SITUBONDO, 2021)
Abstract: This research was conducted to see how is the use of Problem-Based Learning (PBL) and the activity in an online reading course to stimulate critical thinking skills, especially the students who participated in this research. This study used descriptive approach. The sample of this research consist of 6 students from the third semester of English Department in academic year 2020/2021 at one of university in Bogor. To get the data, the researchers used interviews as instruments. The results showed that the implementation of Problem-Based Learning in an online reading course is effective to improve students critical thinking skills and the implementation of learning activities by using Problem-Based Learning model is effective because students could be more understand about the materials and encourage them to solve problems independently or in groups. Keywords: Problem Based Learning, Online Reading Course, Critical Thinking Skills.